Mef2C restrains microglial inflammatory response and is lost in brain ageing in an IFN-I-dependent manner - Aleksandra Deczkowska (Nature Portfolio, 2017)
Microglia cells in the brain regulate immune responses, but in ageing can negatively affect brain function. Here the authors show that the chronic presence of type I interferon in aged mouse brain impedes cognitive ability by altering microglia transcriptome and limiting Mef2C, a microglia ‘off’ signal.